2019
DOI: 10.1136/bmj.k5267
|View full text |Cite
|
Sign up to set email alerts
|

Maximising the impact of patient reported outcome assessment for patients and society

Abstract: Patient reported outcome measures can help drive global patient centred healthcare reform, but we need a more efficient coordinated approach to assessment if we are to fully realise benefits for patients and society, say Melanie Calvert and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
233
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(243 citation statements)
references
References 33 publications
0
233
0
3
Order By: Relevance
“…Considering the evidence reviewed here, we identify two priority areas for further research and development. First, there is an urgent need to establish how to enable the routine collection of patient evaluations of health and health care using patient-reported experience and outcome measures (PREMS and PROMs) and to incorporate these into comprehensive assessment frameworks [21,106,[120][121][122][123][124]. Second, there is a need to advance approaches for the measurement of the role of service users (and their carers) as active partners in service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the evidence reviewed here, we identify two priority areas for further research and development. First, there is an urgent need to establish how to enable the routine collection of patient evaluations of health and health care using patient-reported experience and outcome measures (PREMS and PROMs) and to incorporate these into comprehensive assessment frameworks [21,106,[120][121][122][123][124]. Second, there is a need to advance approaches for the measurement of the role of service users (and their carers) as active partners in service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…There was limited reporting of patient-reported QOL; outcomes were detailed in only two prospective studies 60,62 and one retrospective study 58 , with small patient numbers and short follow-ups for the PMRT groups 58,60,62 . A priori hypothesis-driven selection of QOL domains was absent from methods 58,60,62 , with no reporting of missing data or how this problem was tackled 34 . Three studies 58,60,62 used the BREAST-Q and one 60 used the breast cancer-specific questionnaire (EORTC QLQ-BR23) 42 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…One way to measure what matters to patients is to use patient-reported outcome measures (PROMs) to assess the effects of disease or treatment on symptoms, functioning and health-related QOL 34 . In this systematic review, PROMs were poorly reported and underpowered for overall small effect sizes of individual QOL domains 43 .…”
Section: Cosmetic Outcomesmentioning
confidence: 99%
See 2 more Smart Citations